Analysis of Traditional Elements in Traditional Woven Fabrics Using the ATUMICS Method : Case Study: Sidan Woven Fabric by the Endo Segadok Weaving Group in Menua Sadap Village - Ariseftia, Ega; Azzahra, Alifiansi Nurul Fatimah; Ciptandi, Fajar (Jurnal Indonesia Sosial Sains, 2025)
Knowing about the elements of traditional elements is essential because it can inspire modern design, allowing for innovation while respecting cultural roots. One of the traditional Indonesian woven fabrics that has the potential to be developed and the elements of tradition are known is the Sidan Weaving fabric. Sidan weaving is one of the products made by the indigenous people of the Dayak Iban tribe who come from Kapuas Hulu Regency, West Kalimantan Province. Therefore, the analysis of traditional elements in Sidan woven fabrics of the Endo Segadok weaving group in Menua Sadap Village was carried out to find out a more thorough understanding of Sidan woven fabric products, both in terms of visuals and meanings, so that every detail can be interpreted as part of a valuable cultural heritage and know the potential that can be developed. Data collection was carried out using observation, interview, and literature study methods, then analysis was carried out using the ATOMICS method. The results of the study stated that the results of the analysis of Sidan woven fabrics using the ATUMICS method showed that starting from the production process as a whole, it maintained and revived cultural traditions that had been passed down from generation to generation. Each element of the traditional element not only reflects aesthetics, but also contains a deep symbolic meaning related to the customs, beliefs, and cultural values of the local people.